The Effect of Financial Literacy, Self-Control, and Buy Now Pay Later (BNPL) Usage on Financial Decision-Making Among Generation Z: The Mediating Role of Financial Behavior - Vania Utami; Osly Usman (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
By evaluating the mediating variable of financial behavior, this research investigates how financial literacy, self-control, and the usage of